A fuzzy analytic hierarchy process-based analysis for prioritization of barriers to offshore wind energy. (15th April 2022) - Dhingra, Tarun; Sengar, Anita; Sajith, Shambhu
Abstract: Offshore wind energy is an essential component of the climate system and plays a crucial role in addressing climate change. India has a coastline of seven thousand kilometres and a National offshore wind energy policy; however, the installed capacity of offshore wind energy is yet to start, signalling the existence of significant barriers. The specific objective of this study is to develop a framework for identifying and categorizing the barriers to the growth of offshore wind energy in India. The study prioritizes these barriers using a multi-criteria decision-making approach and sensitivity analysis for robustness. Barriers listed in the technical category emerged through analysis as the significant barriers to the growth of offshore wind energy in India, which includes grid-connection challenges, inadequate technology, lack of servicing and maintenance facilities, inadequate testing and commissioning, cable installation challenges, lack of energy storage, and lack of offshore wind zones. Financial barriers are categorized as the second most crucial barrier: initial capital, credit accessibility, inadequate subsidies, power pricing scheme, immature offshore engineering market, insurance, and imperfect feed-in tariff mechanism. It is followed by social, institutional, geographical, and supply chain barriers. Regulatory and political barriers stand on the last rank and have the most negligible influence on offshore wind energy in India. Highlights: Barriers to the growth of offshore wind energy identified and categorized for India. AHP with Fuzzy logic approach used for prioritization of barriers. Managerial and practical implications for these barriers. Technical barrier most critical barrier to offshore wind energy.